The effect of nitrification inhibitor on the yield and quality of Triticum aestivum L. and Brassica napus L. – A long-term experiment - Antošovský, Jiří; Škarpa, Petr; Ryant, Pavel (Elsevier Science BV, 2025)
Purpose: The nitrogen is a crucial element in crop production, which can be associated with the environmental loss and low agronomic nitrogen efficiency. The utilization of fertilizers with inhibitors represents an economical option by lowering the number of applications, lowering the dose of nitrogen and limiting the risk of environmental loss of N. Methods: The long-term effect of nitrogen fertilizer with nitrification inhibitors (alternative technology) in comparison with conventional fertilizers (prevalent technology) on yield and quality of winter wheat and oilseed rape cultivated in field conditions at two experimental localities was evaluated. Results: The long-term average yields of both crops were significantly higher after the alternative technology with the NI (+0.4 t/ha wheat grain, +0.3 t/ha rape seed) in comparison with prevalent technology. The effect of NI also resulted in significantly higher average protein content (13 %), protein production (0.98 t/ha) and gluten content (29.5 %) in wheat grain in comparison with prevalent technology without NI (12.8 %; 1.04 t/ha; 28.7 %). The oil content of oilseed rape did not differ significantly between the compared fertilizer technologies. The alternative technology with NI resulted in significantly highest production of oil (+0.1 t/ha) in comparison with prevalent technology. The economic evaluation of alternative technology with NI resulted in net profit in comparison with prevalent technology in every scenario. Conclusions: These long-term results are proving, that addition of NI to the conventional fertilizer applied in higher dose and less applications is more suitable choice compared to the classic split nitrogen fertilization.
Keywords: Nitrification inhibitor; Nitrogen; Winter wheat; Oilseed rape; Yield